On Nonoscillation of Advanced Differential Equations with Several Terms - L. Berezansky; E. Braverman (Abstract and Applied Analysis)
Existence of positive solutions for advanced equations with several terms x˙(t)+∑k=1mak(t)x(hk(t))=0,  hk(t)≥t is investigated in the following three cases: (a) all coefficients ak are positive; (b) all coefficients ak are negative; (c) there is an equal number of positive and negative coefficients. Results on asymptotics of nonoscillatory solutions are also presented.